Arterial stiffness improves with effective chemotherapy in patients with lymphoma. (14th October 2021) - Solomou, E; Ioakimidis, N; Terentes-Printzios, D; Koutagiar, I; Pouli, A; Sioni, A; Giannouli, S; Kafouris, P; Metaxas, M; Kalikakis, G; Aggeli, K; Tousoulis, D; et al.
Abstract: Introduction: Arterial stiffness independently predicts cardiovascular risk and has been associated with the presence of inflammation. Chemotherapy-induced cardiac dysfunction is a major contributor to adverse morbidity and mortality rates in cancer patients. There is extensive literature describing the cardiotoxic effects of anti-cancer treatment on left ventricular systolic function, that may be the result of direct effects of the cancer treatment on heart function, or due to an indirect acceleration of atherosclerosis. However there is only little evidence regarding chemotherapy effects on arterial elastic properties. The gold standard for measuring arterial stiffness is carotid femoral pulse wave velocity (cfPWV) and it is calculated as a function of transit time and distance of the pulse wave derived from the carotid and femoral arteries. Purpose: Our aim was to investigate the effect of chemotherapy in aortic stiffness in patients with lymphoma, a malignancy with known high metabolic burden. Methods: Sixty-six patients (22 male, mean age 56 years) with Hodgkin (n=34) or non-Hodgkin lymphoma (n=32) were enrolled in the study. Patients with Hodgkin Lymphoma underwent therapy with Doxorubicin, bleomycin, vinblastine and dacarbazine (ABVD). The interim of their treatment was set at 1 to 3 days prior to initiating the 3rd chemotherapy cycle. Patients with non Hodgkin Lymphoma underwent therapy with cyclophosphamide, doxorubicin, vincristine, and prednisone+rituximab (R-CHOP). Blood pressure (BP) and carotid-femoral pulse wave velocity (c-f PWV) were measured at baseline, interim and after completion of chemotherapy. Results: Changes in systolic and diastolic BP from baseline, to interim phase and 6 weeks post therapy were insignificant (decrease by 3.87±1.37 mmHg p-0.277 and 3.05±0.92 mmHg p-0.422 respectively). Figure illustrates c-f PWV changes from baseline to interim and 6 weeks after completion of chemotherapy. As figure shows, c-f PWV progressively decreased at the interim phase and at 6–8 weeks after chemotherapy completion (by 0.37±0.14 m/s), (overall P-0.010, by ANOVA) The progressive decrease in c-f PWV remained statistically significant after adjustment for age, systolic BP and diabetes (F=5.173, P-0.009). Patients' baseline characteristics are demonstrated in table 1. Conclusion: Carotid-Femoral PWV decreased at 6–8 weeks post chemotherapy in patients with lymphoma, suggesting that aortic elastic properties improve with chemotherapy in these patients. Considering that aortic stiffness increases due to systemic inflammation and that lymphomas are increased metabolic burden tumors, the significant improvement in arterial stiffness implies that the presence of inflammation caused by the malignancy may play a significant role in the arterial stiffness progression. FUNDunding Acknowledgement: Type of funding sources: None.